2020
DOI: 10.1111/1462-2920.14970
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community diversity in the rhizosphere of nickel hyperaccumulator plant species from Borneo Island (Malaysia)

Abstract: Summary The Island of Borneo is a major biodiversity hotspot, and in the Malaysian state of Sabah, ultramafic soils are extensive and home to more than 31 endemic nickel hyperaccumulator plants. The aim of this study was to characterize the structure and the diversity of the rhizosphere bacterial communities of several of these nickel hyperaccumulator plants and factors that affect these bacterial communities in Sabah. The most abundant phyla were Proteobacteria, Acidobacteria and Actinobacteria. At family lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 95 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…This is identified by a previous study that reported how biogeography affects the microbiome composition in three species of Agave from distinct sites (Coleman‐Derr et al ., 2016). Therefore, the interactions among different geographical and environmental conditions can shape the distinct microbial community composition (Lopez et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is identified by a previous study that reported how biogeography affects the microbiome composition in three species of Agave from distinct sites (Coleman‐Derr et al ., 2016). Therefore, the interactions among different geographical and environmental conditions can shape the distinct microbial community composition (Lopez et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, their relative abundances in HL and BQL were higher than those in QS. There are many Acidobacteria species found in soil samples throughout the terrestrial ecosystems, including Acidobacteriaceae , which is capable of adapting to varied environments and using a variety of polysaccharides 47 . These Acidobacteria are usually acidophilic and less likely to compete in the more neutral soil pH environment and thus can be enriched in the acidic soil samples of BQL.…”
Section: Discussionmentioning
confidence: 99%
“…nutrients and oxygen) in the deeper soil layers leading to reduced microbial diversity and biomass (Goebes et al 2019;Jobbágy and Jackson, 2000). However, rhizodeposition can increase microbial activity at deeper soil layers (Lopez et al 2020), potentially leading to different drivers of microbial activity and biomass across soil layers (Blume et al 2002;Loeppmann et al 2016).…”
Section: Introductionmentioning
confidence: 99%